Integration of Science and Faith: Implementation of Management in Islamic Schools - Alfianto, Ilham Fahmi; Istanto, Istanto (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to analyze the management strategy of Islamic schools in integrating Islamic science and values, along with the supporting and inhibiting factors of the integration of science and Islamic values. The research uses a qualitative method with a case study approach at Daarul Qur'an Science High School. Data was obtained through interviews, observations, and documentation. The data received will be analyzed by data reduction, data presentation, and conclusion drawing and verification. The results of the study show that school management strategies are implemented through four stages: planning, organizing, implementing, and evaluation. At the implementation stage, the integration of Islamic values in science learning is applied in a real way, for example, Biology teachers associate the concept of photosynthesis with QS. Yasin:80 to foster awareness of the greatness of God, and Physics teachers instill the value of trust through energy experiments that emphasize the responsibility of man as successors. This integration is strengthened by religious activities such as tadarus and dhuha prayers. Regular evaluations ensure the sustainability of the program. Supporting factors include teacher competence, cottage support, and adequate facilities, while the obstacles are schedule clashes and double curriculum loads. The findings provide an overview that the implementation of structured school management and the integration of Islamic values in science learning are able to strengthen the character of students, improve the quality of the learning process, and become a model for the development of an integrated curriculum that other educational institutions can replicate.